Imaging biomarkers for antiangiogenic therapy in malignant gliomas. (January 2013) - Leu, Kevin; Pope, Whitney B; Cloughesy, Timothy F; Lai, Albert; Nghiemphu, Phioanh L; Chen, Wei; Liau, Linda M; Ellingson, Benjamin M
SUMMARY  The discovery that malignant gliomas produce an excessive amount of VEGF, a key mediator of angiogenesis, has heightened interest in developing drugs that block angiogenic pathways. These antiangiogenic drugs tend to decrease vascular permeability, thereby diminishing tumor contrast enhancement independent of anti-tumor effects. This has made the determination of tumor response difficult, since contrast enhancement on post-contrast T1 -weighted images is standard for assessing therapy effectiveness. In light of these unique challenges in assessing antiangiogenic therapy, new biomarkers have been proposed, based on advanced magnetic resonance techniques and PET. This article outlines the challenges associated with the evaluation of antiangiogenic therapy in malignant gliomas and describes how new imaging biomarkers can be used to better predict response.